Fifteen Years of Sm-p80-Based Vaccine Trials in Nonhuman Primates: Antibodies From Vaccinated Baboons Confer Protection in vivo and in vitro From Schistosoma mansoni and Identification of Putative Correlative Markers of Protection - Zhang, Weidong; Le, Loc; Ahmad, Gul; Molehin, Adebayo J.; Siddiqui, Arif J.; Torben, Workineh; Karmakar, Souvik; Rojo, Juan U.; Sennoune, Souad; Lazarus, Samara; Khatoon, Sabiha; Freeborn, Jasmin; et al. (Frontiers in Immunology, 2020)
Recent advances in systems biology have shifted vaccine development from a largely trial-and-error approach to an approach that promote rational design through the search for immune signatures and predictive correlates of protection. These advances will doubtlessly accelerate the development of a vaccine for schistosomiasis, a neglected tropical disease that currently affects over 250 million people. For over 15 years and with contributions of over 120 people, we have endeavored to test and optimize Sm-p80-based vaccines in the non-human primate model of schistosomiasis. Using RNA-sequencing on eight different Sm-p80-based vaccine strategies, we sought to elucidate immune signatures correlated with experimental protective efficacy. Furthermore, we aimed to explore the role of antibodies through in vivo passive transfer of IgG obtained from immunized baboons and in vitro killing of schistosomula using Sm-p80-specific antibodies. We report that passive transfer of IgG from Sm-p80-immunized baboons led to significant worm burden reduction, egg reduction in liver, and reduced egg hatching percentages from tissues in mice compared to controls. In addition, we observed that sera from Sm-p80-immunized baboons were able to kill a significant percent of schistosomula and that this effect was complement-dependent. While we did not find a universal signature of immunity, the large datasets generated by this study will serve as a substantial resource for further efforts to develop vaccine or therapeutics for schistosomiasis.